A systematic review protocol of injuries and illness across all the competitive cycling disciplines, including track cycling, mountain biking, road cycling, time trial, cyclocross, gravel cycling, BMX freestyle, BMX racing, e-sport, para-cycling and artistic cycling - Thomas Fallon; Thomas Fallon; Neil Heron; Neil Heron (Frontiers Media S.A., 2024)
IntroductionThe sport of cycling has witnessed phenomenal growth over the past decade. Globally, over 200 million television hours across five continents watched the recent inaugural World Championships in Glasgow, in 2023. The Union Cycliste Internationale (UCI), the world cycling governing body, has highlighted its mission to "promote and support research in cycling epidemiology and medicine, especially for the benefit of lesser-known disciplines" within its 2030 Agenda. This paper outlines a proposed protocol to conduct a systematic review that comprehensively analyses and synthesises the existing literature about cycling-related injuries and illness across all competitive disciplines.MethodsThe Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines will be followed through each stage of this systematic review. Cycling is an umbrella term used for many individual disciplines. Investigation of all types of injuries and/or illnesses sustained during training and/or competition among competitive athletes across all disciplines will be included in this review. A computerised, systematic literature search will be conducted in electronic databases MEDLINE, Scopus, Embase, and Cochrane Library. Independent screening by two reviewers in a two-step process: title/abstract screening followed by full-text review. The reference lists of included articles will be searched to identify any other potentially relevant articles. Narrative synthesis and tabular/charted presentation of the extracted data will be included.DiscussionThis protocol paper outlines the methodology to conduct a systematic review of injuries and illness across all competitive cycling disciplines. The aims of outlining this systematic review protocol are to aid research transparency, help reduce publication bias, prevent selective publication, and prevent the selective reporting of results. Future systematic reviews based on the proposed protocol will summarise the known prevalence, incidences, locations and burden of injury and illness across the sport of cycling.Trial RegistrationThis study has been registered with the PROSPERO International Prospective Register of Systematic Reviews (registration number CRD42024502703).